(untitled) (Damascus University Journal of agriculture sciences, 2023)
The experiment was carried out in the network house of the biological control center at Damascus university during the period between February and May of 2021, with the aim of studying the allelopathic effect of the mustard powder Sinapis arvensis in the management of coriander weeds, in addition to comparing the methods of using mustard powder; directly mixed with the soil at a rate of 1/2, 1,2 kg, or use it in an integrated manner with Trifloraline by mixing 1/2 or 1 kg of mustard powder with 1/2 of the concentration of the herbicides, or by passing irrigation water through a bag containing mustard powder only at a rate of 1 kg, or it contains 1kg of powder to which half the concentration of the herbicide is added. Beside the three treatmens where we applied applied herbicide in the advised concentration 7 days before, after and during planting. Through the experiment, it was found that mixing the soil with mustard powder at a rate of 1 kg per 4m2gave the best results, as it delayed the emergence of annual weeds about 40 days after planting, while coriander seeds germinated after 14 days. It also gave significant efficiency in controlling annual weeds, it was 96,6% for the following weeds: red-root amaranth Amaranthus retroflexus, European heliotrope Heliotropium europaeum, common sowthistle Sonchus oleraceus and toothed dock Rumex dentatus, as well as 98% in the control of scarlet pimpernel Anagallis arvensis and mayweed Anthemis palaestina, and 99% in the control of black nightshade Solanum nigrum, While earth smoke Fumaria officinalis was only seen in control treatment, in addition to that it gave efficiency in controlling the perennial weeds, namely common mallow Malva sylvestris, field bindweed Convolvulus arvensis and purple nut sedge Cyperus rotundus, with an efficiency control of 95%, 99,5% and 65,7 respectively. The research concluded to recommend the use of mustard powder at a rate 1 kg/4m2 as a natural herbicide, and could be added half the concentration of trifluralin to 1 kg mustard powder to the field cultivated by coriander and infested by M. indica and C. rotundus.